Genetic Polymorphisms of Alcohol Metabolizing Enzymes and Alcohol Consumption are Associated With Asymptomatic Cardiac Remodeling and Subclinical Systolic Dysfunction in Large Community-Dwelling Asians. (31st August 2017) - Hung, Chung-Lieh; Chang, Shun-Chuan; Chang, Sheng-Hsiung; Chi, Po-Ching; Lai, Yu-Jun; Wang, Shih-Wei; Wu, Yih-Jer; Yeh, Hung-I; Lin, Shing-Jong; Chen, Che-Hong; Mochly-Rosen, Daria; Wang, Li-Yu; et al.
Abstract: Aims: Excessive consumption of alcoholic beverages is associated with cardiac remodeling and cardiomyopathy. We examined the possible association of alcohol use, common Asian genetic variants in genes involved in alcohol metabolism, and cardiac structures/functions alterations. Methods: A prospective, community-dwelling survey among individuals with available complete echocardiography examined the associations of alcohol use, cardiac structure/functions, and three common alcohol metabolizing genetic variants, including aldehyde dehydrogenase 2 ( ALDH2 ), alcohol dehydrogenase 1B ( ADH1B ) and cytochrome P450 (CYP) isoform 2E1 ( CYP2E1 ). Results: Among 1577 participants (mean age: 53 ± 9, 59.7% female), we observed that in subjects with more frequent weekly ethanol intake showed greater left ventricle (LV) mass, more impaired diastolic functions, and reduced global longitudinal strain (GLS), systolic (SRs) and early diastolic strain rates (SRe) ( P <0.05). After propensity matching for clinical confounders ( n = 330:30 for frequent users and non-users), frequent alcohol use and subjects carrying ALDH2 (A/G or A / A), ADH1B ( A/A) or CYP2E1 (T/C or T/T) polymorphisms were all associated with worse GLSRs and GLSRe, with combined alcohol use and any given genetic variant aggravated these associations (all P < 0.05). Finally, we observed Gene–Gene synergistic effects on LV functional decline in frequent alcohol users by using linear mixed effect model (all interaction P < 0.05). Conclusions: Among East Asians, even moderate alcohol consumption can confer subclinical adverse effects on cardiac systolic functions, which was most pronounced in subjects carrying common variants in alcohol metabolizing genes. These findings challenge the notion of beneficial influences of less heavy ethanol consumption on the heart, especially among East Asians. Short summary: This study evaluated the association of level of alcohol consumption and genetic variants in genes involved in alcohol metabolism with changes in cardiac function in East Asians. Even moderate alcohol use conferred subclinical adverse effects on cardiac systolic functions, which were most pronounced in subjects carrying common alcohol metabolizing genes.